2007
DOI: 10.1002/hbm.20497
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the interaction of sensory cortical function and structure

Abstract: Even the healthiest older adults experience changes in cognitive and sensory function. Studies show that older adults have reduced neural responses to sensory information. However, it is well known that sensory systems do not act in isolation but function cooperatively to either enhance or suppress neural responses to individual environmental stimuli. Very little research has been dedicated to understanding how aging affects the interactions between sensory systems, especially cross-modal deactivations or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 58 publications
7
78
1
Order By: Relevance
“…It appears reasonable to assume that the obtained brain activations during the former condition are, at least, partially representative for the latter. Reduced cross-modal deactivations have been detected in older subjects, with respect to visual and auditory processing (Peiffer et al 2009) and a similar age-related increase in multisensory processing has been observed in the context of postural control (Zwergal et al 2012). In view of this evidence for reduced inhibitory interactions between sensory systems, the brain activations we observed are possibly an underestimation of the true activation during standing.…”
Section: Limitationssupporting
confidence: 74%
“…It appears reasonable to assume that the obtained brain activations during the former condition are, at least, partially representative for the latter. Reduced cross-modal deactivations have been detected in older subjects, with respect to visual and auditory processing (Peiffer et al 2009) and a similar age-related increase in multisensory processing has been observed in the context of postural control (Zwergal et al 2012). In view of this evidence for reduced inhibitory interactions between sensory systems, the brain activations we observed are possibly an underestimation of the true activation during standing.…”
Section: Limitationssupporting
confidence: 74%
“…These subjects were a part of a larger study (Peiffer et al, 2009), and these are the same set of subjects used in our previous network analysis study . All the subjects signed a written informed consent, and the original study was approved by the Institutional Review Board of Wake Forest School of Medicine and conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Age-related changes at the lowest level of information processing, such as decline in visual cortex activation, indicate age-related reduction in the efficiency of bottom-up processing (Cabeza et al, 2004;Madden et al, 2002Madden et al, , 1997Peiffer et al, 2009). Apart from general reductions, a loss of neural specificity, so-called dedifferentiation, has been observed in ventral visual brain regions (Park et al, 2004; see also Carp et al, 2010Carp et al, , 2011.…”
Section: Functional Neuroanatomy Of the Working Memory Networkmentioning
confidence: 99%